Biotechnologies for Gene Therapy RNA, CRISPR, Nanobots, and Preclinical Applications - Yun, Yang H.; Yoder, Kristine E. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The purpose of this book is to highlight some of latest developments and applications of CRISPR, RNA, and DNA to treat diseases ranging from cancers to cardiovascular and degenerative disorders. It also features innovations of the delivery methods for nucleic acids ranging from nanodevices made from DNA and pseudo amino acids to viral vectors. This is an ideal book for academics, clinicians, and students interested in gene therapy.
1. Therapeutic potential of microRNAs and their nanoparticle-based delivery in the treatment of liver fibrosis -- 2. MicroRNA as a versatile regulator of Wnt signaling pathway in colorectal cancer -- 3. Small Activating RNA Therapy for Angiogenesis -- 4. Muscular dystrophy therapy using viral vector-based CRISPR/Cas -- 5. CRISPR-Cas based gene therapy to target viral infections -- 6. CRISPR targeting the integrated HTLV-1 virus -- 7. Retroviral vectors for gene therapy of monogenic diseases -- 8. DNA Origami Nanodevices for Therapeutic Delivery Applications.
Keywords: Medical genetics; Biomedical engineering; Biotechnology; Pharmaceutical chemistry; Medical Genetics; Biomedical Engineering and Bioengineering; Biotechnology; Pharmaceutics